onstraints Perceived by Rice Farmers in the Adoption of Rice Production Practices in Southern Province of Republic of Rwanda - Augustin, Nzigiyimana; Nataraju, M.S.; Gowda, V. Govinda (Indian Journal of Extension Education, 2013)
The study conducted in Southern Province of the Republic of Rwanda to document the constraints faced by farmers in  paddy production revealed that respondents expressed technical constraints related to pest and disease control (90%),  farm yard manure (70%), insufficient water for crop irrigation (62.50%); constraints like high cost of inputs, lack of  finance and expensive labor were main financial constraints faced by rice farmers at 48.75 per cent, 45.00 per cent and  41.25 per cent, respectively. Regarding extension and social constraints, half of the respondents (50%) reported lack of  trainings on new technologies of paddy production, lack of proper demonstrations and field visits 46.25 per cent , 86.25  per cent reported low price of rice on market, 47.25 per cent reported lack of crop insurance in case of production loss  caused by natural calamities and 3.75 per cent reported lack of incentive to innovative farmers.
Keywords: Paddy; constraints; rice farmers; adoption